The Evaluation of Therapeutic Residential Care for Adolescents and Young Adults in France: A Systematic Review - Hirot, France; Huas, Caroline; Durand, Damien; Godart, Nathalie (Frontiers in Psychiatry, 2021)
Early psychosocial rehabilitation of young people presenting mental disorders is a major challenge. In France, the therapeutic residential care called "soins-études", combining care and educational provision, in the Fondation Santé des Etudiants de France (FSEF) can have a role in this rehabilitation. After recalling the history and the concept underpinning soins-études in psychiatry, we performed a systematic review of the literature based on the PRISMA statement via a search for quantitative studies soins-études facilities. Eleven quantitative studies on ten different samples of young people hospitalised in psychiatry in FSEF were identified between the opening of the first unit in 1956 and 2016. The young people involved were mostly aged 16 to 20 years, which reflects the curricula covered in the FSEF establishments. These young people generally presented severe chronic psychiatric disorders. Their previous care trajectory had lasted for more than 3 years and 24% to 55% of them had attempted suicide at least once. Their stays lasted more than 6 months. Depending on the severity of the disorders, 44% to 63% of the young people were considered to have improved at discharge. The contribution of soins-études appears valuable for these young people, since there was a clinical improvement for 54% to 74% of them one to fifteen years after their hospitalisation, with resumption of schooling, professional training or entry into employment in 60% to 75% of the cases. These results are compared with data in the international literature concerning therapeutic residential care, and lines for future research are identified.